Pengaruh Idealisme, Relativisme dan Love of Money terhadap Persepsi Mahasiswa Akuntansi atas Perilaku Etis Akuntan - Velinda Sari; Eka Fauzihardani (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to examine of idealism, relativism and love of money on accounting students-of accountants' ethical behavior. The method used in this study is descriptive and primary method with questionnaire. The study sampled 203 accounting students. Sampling techniques using purposive sampling. Data collection is done by disseminating to respondent using google form. In this study, the data was analyzed using multiple regression analysis. The results of this study indicate that idealism has a positive effect on accounting students' perceptions of accountants' ethical behavior, while relativism and love of money have a negative effect on accounting students' perceptions of accountants' ethical behavior.